BEN低周波成分に関する3次元電磁粒子シミュレーション - 三宅, 壮聡; 佐治, 昌哉; 岡田, 雅樹; Taketoshi, Miyake; Masaya, Saji; Masaki, Okada (2017)
第8回極域科学シンポジウム/個別セッション：[OS] 宙空圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OS] Space and upper-atmosphere sciences Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object